Once-daily upadacitinib versus placebo in adolescents and adults with moderate-to-severe atopic dermatitis (Measure Up 1 and Measure Up 2): results from two replicate double-blind, randomised controlled phase 3 trials. Issue 10290 (5th June 2021) - Guttman-Yassky, Emma; Teixeira, Henrique D; Simpson, Eric L; Papp, Kim A; Pangan, Aileen L; Blauvelt, Andrew; Thaçi, Diamant; Chu, Chia-Yu; Hong, H Chih-ho; Katoh, Norito; Paller, Amy S; Calimlim, Brian; et al.
Summary: Background: Upadacitinib is an oral Janus kinase (JAK) inhibitor with greater inhibitory potency for JAK1 than JAK2, JAK3, and tyrosine kinase 2. We aimed to assess the efficacy and safety of upadacitinib compared with placebo for the treatment of moderate-to-severe atopic dermatitis. Methods: Measure Up 1 and Measure Up 2 were replicate multicentre, randomised, double-blind, placebo-controlled, phase 3 trials; Measure Up 1 was done at 151 clinical centres in 24 countries across Europe, North and South America, Oceania, and the Asia-Pacific region; and Measure Up 2 was done at 154 clinical centres in 23 countries across Europe, North America, Oceania, and the Asia-Pacific region. Eligible patients were adolescents (aged 12–17 years) and adults (aged 18–75 years) with moderate-to-severe atopic dermatitis (≥10% of body surface area affected by atopic dermatitis, Eczema Area and Severity Index [EASI] score of ≥16, validated Investigator's Global Assessment for Atopic Dermatitis [vIGA-AD] score of ≥3, and Worst Pruritus Numerical Rating Scale score of ≥4). Patients were randomly assigned (1:1:1) using an interactive response technology system to receive upadacitinib 15 mg, upadacitinib 30 mg, or placebo once daily for 16 weeks, stratified by baseline disease severity, geographical region, and age. Coprimary endpoints were the proportion of patients who had achieved at least a 75% improvement in EASI score from baseline (EASI-75) and the proportion of patients who had achieved a vIGA-AD response (defined as a vIGA-AD score of 0 [clear] or 1 [almost clear] with ≥2 grades of reduction from baseline) at week 16. Efficacy was analysed in the intention-to-treat population and safety was analysed in all randomly assigned patients who received at least one dose of study drug. These trials are registered with ClinicalTrials.gov, NCT03569293 (Measure Up 1) and NCT03607422 (Measure Up 2), and are both active but not recruiting. Findings: Between Aug 13, 2018, and Dec 23, 2019, 847 patients were randomly assigned to upadacitinib 15 mg (n=281), upadacitinib 30 mg (n=285), or placebo (n=281) in the Measure Up 1 study. Between July 27, 2018, and Jan 17, 2020, 836 patients were randomly assigned to upadacitinib 15 mg (n=276), upadacitinib 30 mg (n=282), or placebo (n=278) in the Measure Up 2 study. At week 16, the coprimary endpoints were met in both studies (all p<0·0001). The proportion of patients who had achieved EASI-75 at week 16 was significantly higher in the upadacitinib 15 mg (196 [70%] of 281 patients) and upadacitinib 30 mg (227 [80%] of 285 patients) groups than the placebo group (46 [16%] of 281 patients) in Measure Up 1 (adjusted difference in EASI-75 response rate vs placebo, 53·3% [95% CI 46·4–60·2] for the upadacitinib 15 mg group; 63·4% [57·1–69·8] for the upadacitinib 30 mg group) and Measure Up 2 (166 [60%] of 276 patients in the upadacitinib 15 mg group and 206 [73%] of 282 patients in the upadacitinib 30 mg group vs 37 [13%] of 278 patients in the placebo group; adjusted difference in EASI-75 response rate vs placebo, 46·9% [39·9–53·9] for the upadacitinib 15 mg group; 59·6% [53·1–66·2] for the upadacitinib 30 mg group). The proportion of patients who achieved a vIGA-AD response at week 16 was significantly higher in the upadacitinib 15 mg (135 [48%] patients) and upadacitinib 30 mg (177 [62%] patients) groups than the placebo group (24 [8%] patients) in Measure Up 1 (adjusted difference in vIGA-AD response rate vs placebo, 39·8% [33·2–46·4] for the upadacitinib 15 mg group; 53·6% [47·2–60·0] for the upadacitinib 30 mg group) and Measure Up 2 (107 [39%] patients in the upadacitinib 15 mg group and 147 [52%] patients in the upadacitinib 30 mg group vs 13 [5%] patients in the placebo group; adjusted difference in vIGA-AD response rate vs placebo, 34·0% [27·8–40·2] for the upadacitinib 15 mg group; 47·4% [41·0–53·7] for the upadacitinib 30 mg group). Both upadacitinib doses were well tolerated. The incidence of serious adverse events and adverse events leading to study drug discontinuation were similar among groups. The most frequently reported treatment-emergent adverse events were acne (19 [7%] of 281 patients in the upadacitinib 15 mg group, 49 [17%] of 285 patients in the upadacitinib 30 mg group, and six [2%] of 281 patients in the placebo group in Measure Up 1; 35 [13%] of 276 patients in the upadacitinib 15 mg group, 41 [15%] of 282 patients in the upadacitinib 30 mg group, and six [2%] of 278 patients in the placebo group in Measure Up 2), upper respiratory tract infection (25 [9%] patients, 38 [13%] patients, and 20 [7%] patients; 19 [7%] patients, 17 [16%] patients, and 12 [4%] patients), nasopharyngitis (22 [8%] patients, 33 [12%] patients, and 16 [6%] patients; 16 [6%] patients, 18 [6%] patients, and 13 [5%] patients), headache (14 [5%] patients, 19 [7%] patients, and 12 [4%] patients; 18 [7%] patients, 20 [7%] patients, and 11 [4%] patients), elevation in creatine phosphokinase levels (16 [6%] patients, 16 [6%] patients, and seven [3%] patients; nine [3%] patients, 12 [4%] patients, and five [2%] patients), and atopic dermatitis (nine [3%] patients, four [1%] patients, and 26 [9%] patients; eight [3%] patients, four [1%] patients, and 26 [9%] patients). Interpretation: Monotherapy with upadacitinib might be an effective treatment option and had a positive benefit–risk profile in adolescents and adults with moderate-to-severe atopic dermatitis. Funding: AbbVie.